Heavy Menstrual Bleeding and Underlying Coagulopathy in an Adolescent Hematology Clinic [19B]. (May 2020) - Mulvaney, Kylie T.; Nelson, Anita L.; Escovedo, Michelle; Borzutzky, Claudia
Abstract : INTRODUCTION: Current literature and guidelines suggest evaluation for underlying coagulopathy among adolescents who report heavy menstrual bleeding (HMB). Adolescent women with HMB are found to have higher prevalence of coagulopathy than the general population. Our study highlights the prevalence of hemostatic disorders among adolescents referred to a specialty adolescent hematology clinic for evaluation of HMB. METHODS: This study is a retrospective chart review of women <22 years seen in a joint Adolescent Medicine and Hematology clinic at Children's Hospital Los Angeles from January 1, 2015 to May 22, 2018. The primary inclusion factor was referral for anemia and reported HMB. Following IRB approval, data was collected on menstrual history and diagnosis of coagulopathy. RESULTS: Of 109 referred, 37 (34%) patients were found to have underlying coagulopathy; most commonly diagnosed was von Willebrand Disease (17.4%) then platelet dysfunction (15.6%); 1 patient was diagnosed with hereditary hemorrhagic telangiectasia. Not all patients presented with chronic HMB; 2 patients had histories of a single prolonged menstrual bleeding episode requiring hospitalization, 3 patients had anemia but normal menses, and 3 patients with anemia had prolonged menses but normal flow. The impact of severe HMB on health care utilization was notable; 47 had required prolonged ER stays in the past (43%); 27 required transfusion (25%). CONCLUSION: Our results showed 34% prevalence of underlying coagulopathy among adolescents referred for HMB, which mirrors existing literature. Our findings reiterate the importance of evaluating the source of HMB through formal testing; menstrual history may not be sufficient in the adolescent population.